Intratumoral γδ T‐Cell Infiltrates, Chemokine (C‐C Motif) Ligand 4/Chemokine (C‐C Motif) Ligand 5 Protein Expression and Survival in Patients With Hepatocellular Carcinoma. Issue 3 (17th March 2021) - Zhao, Na; Dang, Hien; Ma, Lichun; Martin, Sean P.; Forgues, Marshonna; Ylaya, Kris; Hewitt, Stephen M.; Wang, Xin Wei
Abstract : Background and Aims: Hepatocellular carcinoma (HCC) is an aggressive malignancy which is often associated with a complex tumor microenvironment attributable to etiology‐induced cellular inflammation. γδ T cells are known to detect and react to chronic inflammation, which is linked to cancer development, progression, and metastasis. Our recent genomic study revealed an increased infiltration of several immune cell types, including γδ T cells, in tumor microenvironments of a Thai HCC subtype associated with a good prognosis. Approach and Results: Here, we quantified the amount of γδ T cells using a γδ T‐cell‐specific gene signature in 247 Chinese HCC patients. We also validated the γδ T‐cell signature in American HCC patients. Additionally, such an association was only found in tumor transcriptomic data, but not in adjacent nontumor transcriptomic data, suggesting a selective enrichment of γδ T cells in the tumor microenvironment. Moreover, the γδ T‐cell signature was positively correlated with the expression of natural killer cell receptor genes, such as NKG2D and cytolytic T‐cell genes granzymes and perforin, suggesting a stronger T‐cell‐mediated cytotoxic activity. Furthermore, we found that the γδ T‐cell‐specific gene expression is positively correlated with the expression of chemokine (C‐C motif) ligand 4 (CCL4)/chemokine (C‐C motif) ligand 5 (CCL5) and C‐C chemokine receptor type 1 (CCR1)/C‐C chemokine receptor type 5 (CCR5), the receptors for γδ T cells. We validated these results using immunohistochemical analysis of formalin‐fixed, paraffin‐embedded tumor biopsies from 182 HCC patients. Moreover, we found evidence of CCL4/CCL5‐mediated recruitment of γδ T cells both in vitro and in a murine orthotopic Hepa1‐6 HCC model. Conclusions: We propose that CCL4/CCL5 may interact with their receptor, CCR1/CCR5, which may facilitate the recruitment of γδ T cells from peripheral blood or peritumor regions to the tumor regions. Consequently, an increasing infiltration of γδ T cells in tumors may enhance antitumor immunity and improve patients' prognosis.